Is grip strength linked to body composition and cardiovascular risk markers in primary schoolchildren? Cross-sectional data from three African countries - Juerg Utzinger; Nicole Probst-Hensch; Honorati Masanja; Uwe Pühse; Bassirou Bonfoh; Ivan Müller; Cheryl Walter; Rosa Du Randt; Stefanie Gall; Siphesihle Nqweniso; Peter Steinmann; Markus Gerber; et al. (BMJ Open)
Objectives Muscular strength represents a specific component of health-related fitness. Hand grip strength (HGS) is used as an indicator for musculoskeletal fitness in children. HGS can also be used as a marker of cardiometabolic risk, but most available HGS data are derived from Western high-income countries. Therefore, this study examines whether HGS is associated with body composition and markers of cardiovascular risk in children from three sub-Saharan African countries.Design Cross-sectional study.Setting Public primary schools (grade 1–4) in Taabo (Côte d’Ivoire), Gqeberha (South Africa) and Ifakara (Tanzania).Participants Data from 467 children from Côte d’Ivoire (210 boys, 257 girls), 864 children from South Africa (429 boys, 435 girls) and 695 children from Tanzania (334 boys, 361 girls) were analysed.Primary and secondary outcome measures Body composition (assessed via bioelectrical impedance analysis) was the primary outcome. Cardiovascular risk markers were considered as secondary outcome. Blood pressure was measured with an oscillometric monitor, and blood markers (cholesterol, triglycerides, glycated haemoglobin) via Afinion point-of-care testing. HGS (independent variable) was assessed with a hydraulic hand dynamometer. Inferential statistics are based on mixed linear regressions and analyses of covariance.Results Across all study sites, higher HGS was associated with lower body fat, higher muscle mass and higher fat-free mass (p<0.001, 3.9%–10.0% explained variance), both in boys and girls. No consistent association was found between HGS and cardiovascular risk markers.Conclusions HGS assessment is popular due to its simplicity, feasibility, practical utility and high reliability of measurements. This is one of the first HGS studies with children from sub-Saharan Africa. There is a great need for further studies to examine whether our findings can be replicated, to develop reference values for African children, to establish links to other health outcomes, and to explore whether HGS is associated with later development of cardiovascular risk markers.Trial registration number ISRCTN29534081.